Enhancing teaching practice in higher education - Pokorny, Helen; Warren, Digby (Sage, 2016)
This book explores ways in which pedagogical research, theory, models and frameworks can be used pragmatically to enhance teaching practice in higher education. It provides practical strategies, ideas, techniques and approaches drawn from literature and real-life experience, using examples from a variety of disciplines.